2019
DOI: 10.1093/jxb/erz240
|View full text |Cite
|
Sign up to set email alerts
|

Phi thickenings in roots: novel secondary wall structures responsive to biotic and abiotic stresses

Abstract: Phi thickenings are specialized secondary walls found in root cortical cells. Despite their widespread occurrence throughout the plant kingdom, these specialized thickenings remain poorly understood. First identified by Van Tieghem in 1871, phi thickenings are a lignified and thickened cell wall band that is deposited inside the primary wall, as a ring around the cells’ radial walls. Phi thickenings can, however, display structural variations including a fine, reticulate network of wall thickenings extending l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Permeability experiments showed that in this orchid, phi thickenings did not limit the apoplastic diffusion of tracers. Thus, in their induction by stress and their apparent function in stabilising the root, the phi thickenings in Miltoniopsis behave in a similar manner to phi thickenings in other angiosperms and gymnosperms [1].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Permeability experiments showed that in this orchid, phi thickenings did not limit the apoplastic diffusion of tracers. Thus, in their induction by stress and their apparent function in stabilising the root, the phi thickenings in Miltoniopsis behave in a similar manner to phi thickenings in other angiosperms and gymnosperms [1].…”
Section: Discussionmentioning
confidence: 85%
“…Phi thickenings have been observed in more than 100 different plant species, including several monocots, diverse dicot families, and numerous gymnosperms [1,4]. That similar structures are present in so many diverse species suggests either that the phi thickenings have arisen multiple times through convergent evolution, or that they are an ancestral characteristic that has been conserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations